Analisis Penerapan Projek Penguatan Profil Pelajar Pancasila Dalam Pengembangan Nasionalisme Peserta Didik di Sekolah - Ronni Juwandi; Enday Nurmahdiah; Fahmi Fakhrudin; Sarinah Sarinah; Lidaeni Ihsani; Harfi Nurachman (Simpati, 2023)
In the era of globalization, the issue of national identity has become very important. The rapid pace of globalization has led to the erosion of national values, especially among the younger generation who are more interested in foreign cultures than their own national culture. This can be seen from the increased interest of children in imported products compared to domestic products. This research uses a qualitative method to describe and find meaning behind this phenomenon, by producing descriptive data in the form of words, both written and spoken (Ratna, 2010: 94). It is hoped that by instilling nationalistic values, the younger generation will be motivated to defend national unity. These nationalistic values can be taught through various methods, including through the learning process in schools and universities. In the learning process, these nationalistic values can be integrated. The analysis of the implementation of the Student Profile Strengthening Project of Pancasila in the development of student nationalism at SMAN 1 Pamarayan involves activities of the Student Profile Strengthening Project of Pancasila which has the themes of "bhineka tunggal ika" and "bela negara" (unity in diversity and defending the nation).